Testing macroecological hypotheses in sandy beach populations: the wedge clam Donax hanleyanus in South America - Risoli, María Cielo (2023)
Large-scale spatial and temporal variability in environmental conditions may result in differences in life-history traits, population demography, and abundance of sandy-beach species. We analyzed the effects of salinity, chlorophyll a (chl a), and sea surface temperature (SST) on population parameters of the wedge clam Donax hanleyanus from 75 South American sandy beaches covering a 15° latitudinal range. Generalized modeling results showed that betweenbeach differences in abundance, population structure, growth performance, productivity, mortality, and individual shell mass were mainly explained by salinity fluctuations, with chl a and SST as secondary contributors, overriding, in most cases, local habitat features (Dean's parameter, grain size, slope). Our results provide valuable insights into macroscale ecological processes, setting a basis to delineate conservation guidelines at large spatial scales that respond to the potential effects of climate variability and change on sandy beach populations.